Background of the neuropathological site in neurocognitive decline in elderly schizophrenic patients. Issue 4 (29th January 2020) - Hirano, Mitsuaki; Iritani, Shuji; Sekiguchi, Hirotaka; Torii, Youta; Habuchi, Chikako; Fujishiro, Hiroshige; Ozaki, Norio; Yoshida, Mari; Fujita, Kiyoshi
Abstract : We herein report the neuropathological findings of a schizophrenic patient who showed cognitive decline and deterioration of psychiatric symptoms in his elderly years. In the neuropathological investigation in this case, Alzheimer‐type pathology and argyrophilic grain pathology were observed. Schizophrenic patients can sometimes show cognitive decline in later life as an intrinsic symptom. However, they may also be complicated with dementia in later life, although these complications in a clinical setting have not been well examined. Few reports have investigated whether or not schizophrenic patients are likely to be complicated with dementia, and the findings remain controversial. We confirmed relatively mild ageing changes neuropathologically in the present case. How much these pathological changes influenced his psychiatric symptoms is unclear, but these changes were thought to have some degree of relevance. We also discuss the relationship between schizophrenia and dementia. We should remain alert to the fact that even schizophrenic patients can contract neurodegenerative diseases as a dual diagnosis in their clinical course and that they can show complicated symptoms. Further investigations of the clinical‐pathological relationship between schizophrenia and dementia are thus needed.